Security Constrained Optimal Power Flow on A 132 kV Line with Service Potential Transformer Substations: A Case Study of Juja-Rabai Line - Joel Mwithui Kitheka (MSD Institute, 2025)
The frequent power outages in transmission lines have been associated with generation station expansion to meet growing power demand without corresponding transmission infrastructure development, leading to exceeded loadability limits and system outages. This paper utilized PowerWorld simulator and a modeled Juja-Rabai power network to analyze secure optimal power flow conditions of a 132 kV transmission line with installed Service Potential Transformer (SPT) substations that address power demand from scattered villages near high voltage lines. The study focused on economic load dispatch of three thermal power plants (Thika, Rabai, and Kipevu) supplying power via conventional and non-conventional substations. Security constrained economic load dispatch, optimal power flow, and security constrained optimal power flow were analyzed under both pre-contingency and post-contingency states, including forced contingency scenarios. The results revealed that generating stations successfully adjusted their economic dispatch to achieve secure and economical operation, eliminating line outage risks. The analysis demonstrated that up to nine SPT substations can be optimally terminated on a 132 kV line while maintaining voltage stability and system security. The SCOPF methodology effectively balanced economic optimization with security requirements, providing a robust framework for transmission system planning in developing countries and supporting the viability of SPT technology for rural electrification.